Changing Cultural Landscapes under the Impact of Exile, Diasporas and Return Migration - Roniger, Luis (Araucaria, 2024)
This article discusses the impact of territorial displacement on Argentina,Chile, Paraguay and Uruguay during the cycle of dictatorships and democratizationof the late twentieth century and early twenty-first century. It points out thecomplexities and different forms of exile, expatriation and migration whichthese societies experienced, while asserting that exile could not be undone fullywith democratization, as many of those who left did not come back, others leftin new waves of expatriation, and even those who did return could not resumewhat had been left behind. Yet, the experience of living elsewhere broadened thesocial, political and cultural perspectives. Whether returning or not, or becomingsojourners, many individuals who left during the dictatorship made substantialcontributions to the societies of origin in domains as varied as politics, arts andletter, science, the publishing industry, education, the state apparatus and theeconomy. Illustrations of such varied impact are presented.